Finding shortest routing solution in mobile AD HOC networks using firefly algorithm and queuing network analysis - Aznida Hayati, Zakaria@Mohamad; Hasni, Hassan; Ahmad Shukri, Mohd Noor (Penerbit UTM Press, 2015)
Mobile ad hoc network (MANET) is a group of mobile nodes establishing a wireless network without using centralized and fixed infrastructure. In MANET, nodes may function as hosts and routers. The nodes can move freely and in arbitrary ways.The network topology in MANET is dynamic because of the frequent mobility of nodes, thus routing is challenging aspects in MANET. Routing protocol plays a role in choosing and selecting the optimal route for transferring the packets of data from the source node to thedestination node efficiently. Mostly the previous routing protocols are not practical to this dynamic network topology. Therefore designing an efficient routing protocol for this dynamic network is vital issue. In this paper, the author has proposed an approach, which selects shortest route for transferring the packets of data from source node to the destination node combining firefly algorithmand queuing network analysis. Firefly algorithm can be applied to find the shortest route in this routing problem. The response times taken to send packets of data can be calculated using the suggested queuing model. The result reveals that attractiveness of node in MANET decreases with the increasing value of response time.